Matrix metalloproteinases regulate extracellular levels of SDF-1/CXCL12, IL-6 and VEGF in hydrogen peroxide-stimulated human periodontal ligament fibroblasts. Issue 1 (May 2015) - Cavalla, Franco; Osorio, Constanza; Paredes, Rodolfo; Valenzuela, María Antonieta; García-Sesnich, Jocelyn; Sorsa, Timo; Tervahartiala, Taina; Hernández, Marcela
Highlights We stimulated hPDLF with H2O2 in the presence/absence of Ilomastat (MMPs inhibitor). Oxidant conditions increased anti-oxidant enzymes, cytokines and MMPs. Oxidant conditions favored cell migration in a MMP-dependent fashion. Ilomastat modified the effects of H2O2 over cytokine levels and reduced cell migration. There is a bidirectional regulation system between MMPs and cytokines.